KEANEKARAGAMAN JENIS TUMBUHAN OBAT DI KAWASAN HUTAN PENDIDIKAN UNIVERSITAS TADULAKO KECAMATAN BULANO LAMBUNU KABUPATEN PARIGI MOUTONG - Delfans, Delfans; Sudhartono, Arief; Korja, I Nengah (Universitas Tadulako, 2019)
Indonesia is estimated to have 100 to 150 families of plants, most of which are used as medicinal plants. The use of traditional medicine is one of the cultures of the people of Wanagading Village, Bulano Lambunu Subdistrict, Parigi Moutong District, but the study of medicinal plants in the region is still lacking. The purpose of this study is to know the diversity of medicinal plants. This research was conducted for 2 months, July to September 2016, in the Forest Education Area of Tadulako University Bulano Lambunu District, Parigi Moutong Regency. The research method is the path method with purposive placement of the initial plot based on the first time found medicinal plants. Made as many as 4 lanes, parallel to the lane one with the other lane, the number of 5 plots with the size of each 20 m X 20 m, the distance between plots in each lane is 25 m, distance of each lane with other lanes 60 m, area of observation 4 ha medicinal plants, based on one location of medicinal plant habitat. The results of the study found 31 types of medicinal plants from 21 families. The type of medicinal plants that dominate the tree level is the type of Ficus benjamina L with INP of 103.90%, at the level of the pole is the type Clerodendrum calamitosum L with INP 82.82%, at the stake level is Morinda citrifolia L with INP 80.01%, at the seedling and understorey level Sida rhombifolia with INP 14.94%. Diversity index value (H ') tree level is 1.47 (medium), diversity index (H') pole level is obtained value 1.72 (moderate), diversity index (H ') stake level is obtained value 1.70 (medium) , diversity index (H ') at seedling level was obtained 3.00 (medium).Keywords: diversity of medicinal plants.